Adolescents at Serious Psychosocial Risk: What Is the Role of Additional Exposure to Violence in the Home?. Issue 6 (March 2018) - Díez, Cristina; Fontanil, Yolanda; Alonso, Yolanda; Ezama, Esteban; Gómez, Laura E.
Research into the effects of interpartner violence on the psychosocial development of the children of maltreated mothers is a relatively new field. This work examines the impact of exposure to interpartner violence (EIPV) on minors in middle and late adolescence, where this vicarious maltreatment is in addition to other situations of severe psychosocial risk. A group of adolescents who had suffered various types of direct maltreatment were compared with another group who, in addition to experiencing direct maltreatment, had mothers who had also been the victims of interpartner violence. There were 276 participants in total (138 adolescents and their mothers) reporting via questionnaires about their experiences related to maltreatment and about maladaptation and psychological dysfunction. The results demonstrate significant dysfunction in the adolescents, especially as indicated in the mothers' reports. In addition, the results make it clear that the adolescents are actively and directly involved in the episodes of interpartner violence and that the additional negative impact of vicarious maltreatment is evident in almost every aspect of their lives. Only the attitude toward teachers scored worse in the no-EIPV group. EIPV minors scored higher on personal and social maladjustment and worse on adaptive skills, and showed a more marked tendency to internalize problems. This study emphasizes the importance of considering EIPV as a form of child maltreatment and including it in programs of protection and intervention.